Gibberellin Localization and Transport in Plants. (May 2018) - Binenbaum, Jenia; Weinstain, Roy; Shani, Eilon
Abstract : Distribution patterns and finely-tuned concentration gradients of plant hormones govern plant growth and development. Gibberellin (GA) is a plant hormone regulating key processes in plants; many of them are of significant agricultural importance, such as seed germination, root and shoot elongation, flowering, and fruit patterning. Although studies have demonstrated that GA movement is essential for multiple developmental aspects, how GAs are transported throughout the plant and where exactly they accumulate remain largely unknown. Here, we summarize recent findings from studies of GA movement and localization, and discuss the importance of GA intermediates in long- and short-distance movement. We further review recently identified Arabidopsis GA transporters and highlight their complex specialization and robust functional redundancy in GA transport activity. Highlights: Bioactive gibberellin (GA) can form local accumulation maxima, for example in the root elongation zone and in the hypocotyl, which correlate with cellular growth. GA movement is necessary at multiple developmental stages including germination, root elongation, the transition to flowering, and flower development. Long-distance movement of GA seems to be mostly restricted to its nonbioactive precursors rather than to bioactive forms. Proteins from the NPF and SWEET families were recently identified and shown to transport GA in planta . Thus far, identified GA transporters are redundantly robust on the one hand, but have diverse substrate specificity for bioactive GAs, their precursors, and other signaling molecules on the other.